Form Tutors in the Joint Teaching of Music: Perspectives and Experiences - Teresa Sarmento; Fernanda Martins (LED Edizioni Universitarie, 2015)
In the Portuguese school system, form tutors (FTs) are an intermediate education management structure. The form tutor is responsible for a position of coordination and orientation with a «threefold function»: a relationship with students, relationship with the student's family and relationship with other class teachers. The joint teaching of music is a part of the educational system in basic education. It is optional and provides musical and instrumental training to students who are interested in taking it. In order to achieve this, there is a system, subject to protocols, between general education schools and schools specializing in teaching music. There is also the position of FT in specialized schools and it also includes a «threefold function». However, these FTs have the additional role of representing music teachers at the class council, which is held at the general education school. Thus, in these cases, both FTs have a fourth joint area, between the music school and the general education school, which makes the relationship between them even more complex. This paper is based on the analysis of empirical data obtained from the testimonies of FTs regarding their representations and experiences in leadership and the coordination of teachers among schools in which there is a joint teaching system. The aim of collecting narratives is to look into some of the main challenges and confrontations related to leadership issues, which we assume to be the focus of those who have the role of form tutor in that specific context.